Duplex detection of avian and chicken using common primer-PCR in processed meat products - Mohamad, Nurhidayatul Asma; Khairil Mokhtar, Nur Fadhilah; Mohd Desa, Mohd Nasir; Hanapi, Ummi Kalthum (Universiti Teknologi MARA Pahang, Malaysia, 2024)
Meat fraudulent practice has been proven to damage the quality of the food and consumer’s health. Being widely available at lower cost, chicken meat has been frequently used as meat substitute in meat-based food products. As a solution, a duplex polymerase chain reaction (PCR) assay employing a common primer coupled with a unique adapter sequence was developed for simultaneous chicken-speciﬁc and avian universal detection. The assay targeting 322 and 219 bp of melanocortin 1 receptor (MC1R) gene sequence respectively was optimized with high speciﬁcity against a range of avian and meat species, and high LOD of 0.01 ng. Across forty-two commercial meat products tested, chicken meat was detected in seven non-avian samples where only two of them declared the presence of chicken meat in the label. The practical duplex PCR assay can be potentially applied for routine practice for qualitative investigation of contamination or adulteration in processed meat products.